Adaptabilidade, estabilidade e relações entre caracteres de trigo em ensaios multiambientes - Tischler, André Luís (2021)
Wheat (Triticum aestivum L.) is one of the most important cereal in the world because of the large amount of by-products originated. However, in Brazil, the cultivated area is still limited by environmental, economic and productive factors that in many cases result from the lack of information about environments and genotypes. Therefore, research in relation to the breeding and application of biometric and multivariate analysis, especially where the culture is rising, are essential for the progress of the culture and increasing production area. In this context, the objective of this study was to evaluate the adaptability, stability, grain yield and the relationships between morphological and productive characters of wheat genotypes subjected to different cultivation environments. The tests were conducted in the experimental area of the Federal Institute of Education, Science and Technology Farroupilha in São Vicente do Sul, in the agricultural years 2016, 2017 and 2018, and were composed of four genotypes: TBIO Sintonia, TBIO Sinuelo, TBIO Sossego and TBIO Toruk, and for three sowing seasons each year, carried out between the months of May, June and July. The characterization of the genotypes in the environments were performed through individual and joint analysis, AMMI, REML/BLUP, WAASB and WAASBY and the relationships between characters were investigated through Pearson correlation, path analysis and canonical correlation analysis to identify whether the responses of these methodologies and characters changed when related. The results show that between environments there was great environment variation and the ranking of genotypes in terms of production changes according to the methodology used. Likewise, the relationships between characters also changed according to the conditions observed in the environments. Adaptability and stability are satisfactorily predicted by WAASB and WAASBY methodologies through the association of performance and characters performance with grain yield. The TBIO Sinuelo genotype was the most productive in most environments, but the most stable and adapted genotype was TBIO Sossego, and the most unstable and least adapted was TBIO Sintonia. The linear relationships between characters show positive correlations between length and number of spikelets in the main ear, length and number of spikelets in the ear of the tiller, as well as for the number of spikelets in the main ear and tiller in relation to the number of grains of these. The most suitable characters for direct and indirect selection for the improvement of wheat plants were number of grains in the ear of the tiller and impurity, while hectoliter weight and thousand grain mass are the most recommended considering only indirect selection in these tested environmental conditions. The canonical correlations between the morphological and productive groups are dependent in most environments and larger plants with greater length of the main ear and greater length of the ear of the tiller can be indirectly associated to increase the grain yield.